Deformation Signals at Mud Volcano in Kambing Island Detected by L-band InSAR - Naufal Setiawan; Masato Furuya (Jurnal Ilmiah MTG, 2022)
Abstract – Mud volcanoes are generated by fluid and solid material extrusion from their mud reservoir and are predominantly found at convergent plate margins. Kambing Island is a small island in Eastern Timor, Indonesia, where the Australian continental plate collides with the Banda Sea plate. The previous geological study identified active mud volcano on this island, but it is still unclear whether and to what extent they are active. In this work, we attempt to detect surface deformation due to the mud volcanoes activism in Kambing island using the Advanced Land Observing Satellite/ Phased Array Type L-band Synthetic Aperture Radar (ALOS/PALSAR) Interferometry Synthetic Aperture Radar (InSAR). The ALOS/PALSAR datasets consist of 12 ascending and 5 descending Synthetic Aperture Radar (SAR) data from 2006 to 2011. Although the results indicate surface deformation signals are hardly detected in the interferogram pairs due to lost coherence and atmospheric noise, we could highlight the episodic occurrence of surface deformation signals between April and November 2008 reaches 6.4 cm moving away from the satellite line of sight. In the future, to back up our findings, further field surveys or long-term InSAR are needed. Keywords: mud volcano, InSAR, deformation.